Things that go - Sirett, Dawn; Harvey, Victoria; Palastanga, Victoria (London Dorling Kindersley Limited, 2010)
"Stroke, tickle and touch the textures together with your baby and help them discover all about things that go. Let their little hands roam and feel how shiny the tractors are and how dusty the diggers feel. They'll learn as you play. Twinkly, bumpy, scaly, silky, sandy, sticky and shiny textures in a chunky package: perfect for encouraging tiny fingers to explore and tiny minds to develop."--Publisher description
picture books
1 2 13 23
Keywords: Things that go -- Juvenile literature